Genre Analysis of Research Abstract: A Literature Review - Nita Sari Narulita Dewi; Violintikha Harmawan (Siliwangi University, 2022)
The presence of an abstract is required in a research publication, and it is a recurring problem for graduate students. The purpose of this literature review article is to elucidate on the following topics by evaluating relevant research publications published in respectable journals between 2014 and 2021: (1) tendency of rhetorical move usage, (2) linguistic features usage in rhetorical moves, and (3) pedagogical implications of rhetorical moves on teaching writing. In previous studies, the following conclusions were confirmed:(1) rhetorical move usage is categorized as obligatory moves and supplementary moves, (2) linguistic features usage in rhetorical moves includes grammatical tense usage, voice form usage, metadiscourse marker, and grammar complexity, and (3) In several research, rhetorical moves yielded positive effects in teaching writing, especially for academic writing instruction and research. This study recommends that more extensive research be conducted, concentrating not just on the moves and steps but also on genre development and their implications. Furthermore, further research is expected to gain a deeper investigation into how genre analysis can improve one’s writing quality. Keywords: genre analysis, rhetorical moves, research abstract.